General anaesthetic agents do not influence persistent pain after breast cancer surgery. Issue 10 (October 2015) - Lefebvre-Kuntz, Danièle; Dualé, Christian; Albi-Feldzer, Aline; Nougarède, Bertrand; Falewee, Marie-Noëlle; Ouchchane, Lemlih; Soule-Sonneville, Sylvie; Bonneau, Julie; Dubray, Claude; Schoeffler, Pierre
<x xml:space="preserve">Abstract</x> BACKGROUND It has recently been suggested that propofol exerts a protective effect on the occurrence of persistent pain after breast cancer surgery. We analysed data from a subcohort taken from a multicentre study to validate this information. OBJECTIVE The objective of this article is to study the role of the agent used for maintenance of general anaesthesia on the occurrence of persistent pain, with adjustment for multiple pre and peri-operative variables using the generalised linear model. DESIGN A prospective cohort study. SETTING Four French university hospitals. PATIENTS Three hundred and twenty-eight and 362 patients with full dataset, depending on the studied outcome. INTERVENTION Questionnaires sent at the third and the sixth month after surgery. MAIN OUTCOME MEASURES The risk of persistent postsurgical neuropathic pain (defined by the DN4 questionnaire) within 6 months after surgery, and the intensity of persistent pain at the sixth month. RESULTS Axillary lymph node harvesting and previous history of peripheral neuropathy were independent risk factors of persistent postsurgical neuropathic pain, although older age was protective. The same independent risk factors, but not age, explained the intensity of persistent postsurgical pain at the sixth month after surgery. We did not find any effect of the general anaesthetic, whether halogenated agent or propofol, using either unadjusted or adjusted analyses based on covariates or propensity score. CONCLUSION There does not appear to be a role for the anaesthetic protocol in the occurrence of persistent postsurgical pain. Other already well established hypotheses were confirmed. TRIAL REGISTRATION ClinicalTrials.gov (ref. NCT00812734).